Diseño del sistema de gestión de seguridad y salud en el trabajo según la iso 45001 de 2018, para la empresa industrias de guantes y suministro “Joab Caleb” (2024)
The main objective of the subsequent research work is to carry out an occupational health and safety management design for the JOAB CALEB gloves and supplies industries company, which has as its problem the lack of an SG-SST, the implementation of This will be contemplated under the ISO 45001 2018 standard, which will have as its main criterion for compliance, evaluating the state of the organization through an initial evaluation and with the results of the same, the design is carried out, taking into account the requirements of the standard. . The organization is aware of the lack of the system, which is why it decides to start with the design of the management system; The analysis shows us that there are no suitable procedures for the adequate development of activities within the organization, that is, the regulations stipulated by law are not being complied with and this could lead to legal problems for the organization. glove and supply industries, JOAB CALEB, thanks to this design, will have the current legal requirements of an SG-SST which will help it keep track of hazards, accidents, incidents and occupational diseases, in addition to having all the documentation required to each activity to be carried out.